PENGARUH PENERAPAN MEDIA PEMBELAJARAN KARTU KUARTET BER- BARCODE TERHADAP MINAT BELAJAR PENDIDIKAN PANCASILA SISWA KELAS X SMAN 4 PEKANBARU - Sindy Safitri; Haryono; Indra Primahardani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low interest of students in learning at school, especially in the subject of Pancasila Education. Lack of learning innovation is one of the main causes. Therefore, the implementation of barcode quartet card learning media as an effort to increase students' interest in learning. The formulation of the problem in this study is whether there is an effect of the implementation of barcode quartet card learning media on the interest in learning Pancasila Education students of class X SMAN 4 Pekanbaru. The purpose of this study is to determine the effect of barcode quartet card media on students' interest in learning. This study is expected to provide scientific contributions in the field of education and become a theoretical basis in the development of Pancasila Education learning. The study used a quantitative method with a true experimental design. The location of the study was at SMAN 4 Pekanbaru, Jalan Adi Sucipto No. 67. The population consisted of all 416 class X students. The sample was determined through random sampling technique, obtaining two homogeneous classes with a total of 84 students. The results of data analysis showed that there was a positive and significant influence between the use of barcode quartet card media and students' interest in learning. The calculated t value = 2.830 > t table = 1.663 and sig. (2-tailed) = 0.006 < 0.05. Thus, the Ha hypothesis is accepted. In conclusion, the barcode quartet card media is effective in increasing the interest in learning Pancasila Education of class X students of SMAN 4 Pekanbaru.